Prenuclear L∗+H Activates Alternatives for the Accented Word - Braun, Bettina; Biezma, María (Frontiers in Psychology, 2019)
Previous processing studies have shown that constituents that are prosodically marked as focus lead to an activation of alternatives. We investigate the processing of constituents that are prosodically marked as contrastive topics. In German, contrastive topics are prosodically realized by prenuclear L*+H accents. Our study tests a) whether prenuclear accents (as opposed to nuclear accents) are able to activate contrastive alternatives, b) whether they do this in the same way as constituents prosodically marked as focus with nuclear accents do, which is important for semantic modeling and c) whether the activation of alternatives is caused by pitch accent type (prenuclear L*+H as contrastive accent vs. prenuclear L+H* as non-contrastive accent) or by differences in F0-excursion (related to prominence). We conducted two visual-world eye-tracking studies, in which German listeners heard declarative utterances (e.g., The swimmer wanted to put on flappers) and watched displays that depicted four printed words: one that was a contrastive alternative to the subject noun (e.g., diver), one that was non-contrastively related to it (e.g., sports), the object (e.g., flappers), which had to be clicked, and an unrelated distractor. Experiment 1 presented participants with two naturally produced intonation conditions, a broad focus control condition with a prenuclear L+H* accent on the subject and a contrastive topic condition with a prenuclear L*+H accent. The results showed that participants fixated more on the contrastive alternative when the subject was produced with an L*+H accent, with the same effect size and timing as reported for focus constituents. Experiment 2 resynthesized the stimuli so that peak height and F0-excursion were the same across intonation conditions. The effect was the same, but the time course was slightly later. Our results suggest that prenuclear L*+H immediately leads to the activation of alternatives during online processing, and that the F0-excursion of the accent lends little. The results are discussed with regard to the processing of contrastive focus accents and theories of contrastive topic.